Application of Quantum Teaching Method to Increase Student Motivation in Islamic Religious Education Subjects: (Case Study in SMP Plus Bani Adam Hawwa Garut Class VIII) - Hilda Ainissyifa; Yufi Mohammad Nasrullah; Nurul Fatonah; Maryam Ayu Ningsih (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2023)
This research explains the application of the quantum teaching method to increase student learning motivation in Islamic religious education subjects. To know how to increase student motivation in learning before and after the application of the quantum teaching method. The method used in this study is a Quasi ExperimentQuasi-Exp mentality Nonequivalent Control Group Design. The sampling technique in this study is a nonprobability sampling technique using total sampling (census) with class VIII A as the experimental class and VIII B as the control class. Data collection techniques in this study were carried out with 1) interviews, 2) documentation, 3) tests (pretests and posttests), and 4) dissemination of questionnaires. Data collection techniques in the form of pretests and posttests are intended to measure the increase in student learning motivation. The results obtained from this study show that there is a significant influence of the application of learning methods in quantum teaching on increasing learning motivation. This is evidenced by the acquisition of the average posttests value of the experimental class is 80, while the average value of the control class is 70. The statistical tests result obtained T hitung 2.13 and T label value is 1.99, where the T hitung > Ttabel then Ha is accepted, this means that there are differences and increases in student motivation in learning before and after the application of the quantum teaching method in Islamic religious education subjects.